(untitled) (Tanzania Medical Journal, 2025)
Introduction The Coloboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and development, Genitourinary anomalies, and Ear abnormalities (CHARGE) syndrome is a rare, autosomal dominant but usually sporadic condition with an estimated prevalence of 1 in 100,000 births. An early diagnosis of CHARGE syndrome is challenging especially in our settings with the absence of advanced genetic testing thus leading to neglect and under-reporting of similar cases. We highlight application of the existing modified diagnostic criteria to diagnose CHARGE cases in resource-limited settings like ours, where genetic testing is difficult to access. Case Presentation We report a male African neonate born at term and referred from a nearby district hospital immediately post-delivery due to respiratory distress with cyanosis and multiple congenital anomalies. He was noted to have dysmorphic features, bilateral microphthalmia, and severe microtia with facial palsy. He also had ankyloglossia and hypertelorism of the nipples and was noted to have a unilateral right-sided choanal atresia after failure to pass a nasogastric tube and cotton wisp test. Cardiovascular and genitourinary screening detected conotruncal heart defect and unilateral cryptorchidism with left solitary kidney respectively. Based on his presentation and workup that could be completed in the ward, there was a high index of suspicion of CHARGE syndrome. Application of the updated Blake criteria revealed several major and minor features consistent with the diagnosis, to be confirmed on further multidisciplinary workup. The infant was discharged home in relatively stable condition during the second week of life, with planned follow-up at the cardiology, ophthalmology, and ENT clinics. Unfortunately, he passed away at home before definitive interventions could be initiated, likely due to complications related to his underlying condition. Conclusion In low-resource settings like ours, the absence of diagnostic facilities and limited management resources, often means neonates presenting with multiple congenital anomalies go without a confirmed diagnosis or timely multidisciplinary intervention. This can lead to unintentional neglect and delayed escalation of care. However, application of existing updated CHARGE syndrome criteria can serve as a valuable tool to support early recognition and guide initial management potentially preventing avoidable deaths in these patients.